Operation and Maintenance of Thermal Power Stations Best Practices and Health Monitoring - Chanda, Pradip; Mukhopaddhyay, Suparna; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
This book illustrates operation and maintenance practices/guidelines for economic generation and managing health of a thermal power generator beyond its regulatory life. The book provides knowledge for professionals managing power station operations, through its unique approach to chemical analysis of water, steam, oil etc. to identify malfunctioning/defects in equipment/systems much before the physical manifestation of the problem. The book also contains a detailed procedure for conducting performance evaluation tests on different equipment, and for analyzing test results for predicting maintenance requirements, which has lent a new dimension to power systems operation and maintenance practices. A number of real life case studies also enrich the book. This book will prove particularly useful to power systems operations professionals in the developing economies, and also to researchers and students involved in studying power systems operations and control. .
Chapter 1. Introduction -- Chapter 2. Performance Parameters of Power Stations of Global/Indian Scenario -- Chapter 3. Residual Life Assessment -- Chapter 4. Coal Fired Unit- Operation Guidelines -- Chapter 5. Managing Thermal Stress -- Chapter 6. Chemical Health of Thermal Power Unit -- Chapter 7. Maintenance Practice -- Chapter 8. Outage Minimization -- Chapter 9. Managing Efficiency -- Chapter 10. Best Practices -- Annexures: Important Operation Guidelines/Operation Directives.
Keywords: Electric power production; Energy policy; Energy and state; Electrical Power Engineering; Mechanical Power Engineering; Energy Policy, Economics and Management